The administrative officials of the Pamantasan ng Lungsod ng Maynila as viewed by selected members of the academic staff - Civilize, Soontharee 1948- (s.n.], 1973)
Sixty-three selected faculty members viewed their administrative officials during the second semester of school year 1972-1973 along five dimensions: decision making, communications, personnel relations, professional values, and attitudes towards change. The President, the Arts and Sciences dean, and the Officer-In-Charge of the College of Business Education are viewed as quite cognizant of the institution's history and its implementations for present and future directions, while the Nursing dean is viewed as very cognizant. The president is looked at as a somewhat accurate representative of the school; the Arts and Letters dean and the Business Education head as quite accurate and the Nursing dean as very accurate. The president and the Arts and Letters dean are quite discreet in choosing faculty members, the Nursing dean very discreet and the Business Education dean head quite careless in seleting faculty. All the officials are quite interested and concerned with new findings and ideas, quite innovative and active change agents with the nursing dean excelling in these dimensions.